LEAF ANATOMY OF ARTABOTRYS SUAVEOLENS BLUME VAR. SUAVEOLENS AND ARTABOTRYS SUAVEOLENS BLUME VAR. PARVIFLORUS MIQUEL (ANNONACEAE) - Rugayah Rugayah; Eka Fatmawati Tihurua (PTTI, 2011)
Rugayah & Eka Fatmawati Tihurua. 2011. Leaf anatomy of Artabotrys suaveolens Blume var. suaveolens and Artabotrys suaveolens Blume var. parviflorus Miquel (Annonaceae). Floribunda 4(2): 54–56. — The result of leaf anatomical study indicates that there is no distinctive difference between Artabotrys suaveolens Blume var. suaveolens and A. suaveolens Blume var. parviflorus Miquel, so that the two varieties should be merged.